Environmental preservation from maqasid shariah and islamic perspective: A literature review - Nur Wahida Md Taha; Betania Kartika Muflih; Mohammad Aizat Jamaludin (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Environmental preservation has became one of the core topic to be addressed due to today’s global warming and continuous climate shift. In Islam, environmental preservation is firmly part of Islamic priorities where Allah has entrusted human with the earth and its resources. This includes the balance of resources management and distribution, sustainable practices and conservation and preservation. The purpose of this article is to explore environmental ethics and its well-being through the viewpoint of Islamic teachings and principles. This study used narrative literature review to provide a more comprehensive overview of how Islamic teachings and principles has put environment as important as the well-being of mankind. This article shows that Islam views environment as an important element in life sustainability. Quranic verses, hadith and Islamic jurisprudence perceive environmental preservation as not only a matter of individual ethic but also considered it as religious obligation. The five dharuriyyat in Maqasid Shariah also are strongly associated with environmental preservation and plays a big role in achieving its of each maqasid. Thus, it is concluded that environmental preservation is indeed a holistic responsibility to every person on earth where the condition of environment is depending on the human’s action and behavior. If the humans govern the earth with good regulations then the well being of environment is highly guaranteed. Likewise, the corruption and humans’ greed will cause damages to the earth.